INTRODUCTION - GRIGORE, Mihai-D. (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2023)
Christianity is, by definition, a religion whose existence in the form we know today absolutely depends on mobility. In sociological theories, mobility is regarded as a summative term for processes and aspects of movement: in this sense, one speaks of spatial, temporal, social, cultural, or generational movement processes in both synchronic and diachronic perspectivation. On the one hand, these are aspects of physically moving in space, but there is as well a complex social mobility, which is described as “social change and shifting of social system coordinates.” Together with the so-called mobilities turn, mobility is becoming a broad category of interdisciplinary scholarship. A distinction is made between diverse “mobilities”, which, however, usually interlock and are difficult to research independently of each other.